UPAYA MENINGKATKAN KEMAMPUAN PEMAHAMAN MATEMATIS PESERTA DIDIK KELAS X MIA 2 MAN 2 MODEL PEKANBARU MELALUI PENERAPAN DISCOVERY LEARNING - Susanti, Elsa Susanti; Murni, Atma Murni; Anggraini, Rini Dian Anggraini Dian (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research is based on the low mathematical understanding ability of students in class X MIA 2 of MAN 2 Model Pekanbaru. Based on test mathematical understanding ability for sequence and series lesson there are 5 of 19 students(26,31%) who achieved the mastery. The type of this research is classroom action research and the purpose of this research is to improve the learning process and increase mathematical understanding ability by implementing discovery learning. The subject of this research were the students in class X MIA 2 of MAN 2 Model Pekanbaru at the second semester of academic year 2014/2015. Students in this research are 19 people, there are 9 boys and 10 girls. The instruments of data collection in this research were observation sheets and mathematical understanding ability tests.The observation sheets were analyzed in qualitative descriptive and mathematical understanding ability tests were analyzed in quantitative descriptive. Based on analyzed showed that there are: (1) the improvement of learning process after the implementation of discovery learning in mathematics in class X MIA 2 of MAN 2 Model Pekanbaru by analyzed observation sheets; (2) increase the mathematical understanding ability of students with the score N-gain is 0,66(medium classification) in the first cycle and 0,73 (high classification) in the second cycle. The conclusion of this research is the implementation of discovery learning can improve the learning process and increase the mathematical understanding ability of students in class X MIA 2 of MAN 2 Model Pekanbaru in the second semester of academic year 2014/2015 for opportunity lesson. Key Word : Mathematical Understanding Ability, Discovery Learning, Clasroom Action  Research